2D MoS2 nanosheets on 1D anodic TiO2 nanotube layers: an efficient co-catalyst for liquid and gas phase photocatalysis - Motola, Martin; Baudys, Michal; Zazpe, Raul; Krbal, Miloš; Michalička, Jan; Rodriguez-Pereira, Jhonatan; Pavliňák, David; Přikryl, Jan; Hromádko, Luděk; Sopha, Hanna; Krýsa, Josef; Macák, Jan (Royal Society of Chemistry, 2019)
One-dimensional TiO2 nanotube layers with different dimensions were homogeneously decorated with 2D MoS2 nanosheets via atomic layer deposition and employed for liquid and gas phase photocatalysis. The 2D MoS2 nanosheets revealed a high amount of exposed active edge sites and strongly enhanced the photocatalytic performance of TiO2 nanotube layers.
Keywords: TiO2 nanotube layers; atomic layer deposition; nanosheets